1994
DOI: 10.1002/cyto.990180404
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia‐associated changes identified by quantitative flow cytometry: I. CD10 expression

Abstract: We have compared CDlO antigen expression in normal fetal bone marrow with that of B-lineage acute lymphoblastic leukemia (ALL). Both quantitative indirect immunofluoresence (QIFI) and direct immunofluorescence (IF) tests with Quantum beads were used to convert median fluorescence intensity (MFI) values into numbers of antigen molecules expressed per cell (AgE). Lymphoid precursors in the fetal marrow and liver expressed 3-12.5 x lo3 CD10 molecules/cell with an upper limit of 5 x 104/cell (MaxAgE). The median C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 31 publications
1
87
2
2
Order By: Relevance
“…13,15 Furthermore, the determination of aberrant phenotypic patterns can also allow for minimal residual disease (MRD) monitoring. 17,19 AML with t(8;21) is characterized by a unique molecular abnormality, the AML1-ETO fusion gene. It has been shown that AML1-ETO protein can regulate the transcription of many genes important for hematopoiesis including the M-CSF receptor, the G-CSF receptor and BCL2 (all upregulated) as well as GM-CSF, TCR subunits (a, b and d), NP3 and MDR1 (all downregulated).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,15 Furthermore, the determination of aberrant phenotypic patterns can also allow for minimal residual disease (MRD) monitoring. 17,19 AML with t(8;21) is characterized by a unique molecular abnormality, the AML1-ETO fusion gene. It has been shown that AML1-ETO protein can regulate the transcription of many genes important for hematopoiesis including the M-CSF receptor, the G-CSF receptor and BCL2 (all upregulated) as well as GM-CSF, TCR subunits (a, b and d), NP3 and MDR1 (all downregulated).…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite support for the existence of a unique immunophenotype in AML with t(8;21), quantitative immunophenotyping in this form of AML has rarely been reported. 13 Recent reports have suggested that quantitative immunophenotyping may enhance the diagnosis of leukemias with specific cytogenetic abnormalities [15][16][17] and help define aberrant immunophenotyping patterns that could be useful for monitoring minimal residual disease. [17][18][19] It has also been suggested that quantitative immunophenotyping can contribute to our understanding of the pathogenesis of acute leukemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous publications support the relevance of FI determination in diagnostic, differential diagnosis, prognostic evaluation, and therapy monitoring of leukemias and lymphomas (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 95%
“…7d), the cells are CD8 ϩ T cells with extra low-level (20 ϫ 10 3 ) CD4 display (monoclonal chronic T chronic lymphoid leukemia?). These simple quantitative methods, based on normal blood standards and on stabilized blood preparations, have a wide application in precisely characterizing the aberrant display of various antigens in leukemia and lymphoma (45).…”
Section: Standards For Quantitative Flow Cytometrymentioning
confidence: 99%